2009
DOI: 10.1200/jco.2009.27.15_suppl.5586
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of weekly neoadjuvant chemotherapy followed by radical chemoradiation for locally advanced cervical cancer

Abstract: 5586 Background: Chemoradiation (CRT) is the standard of care for locally advanced cervical cancer but survival is poor among women with large tumours, advanced stage, or positive nodes. Neoadjuvant chemotherapy (NACT) prior to CRT to down-stage tumours and lengthen the exposure to systemic treatment is designed to improve outcome. Methods: Patients (pts) with locally advanced cervical cancer received dose-dense carboplatin (AUC2) and paclitaxel (80 mg/m2) weekly, for 6 cycles, followed by CRT (external and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The overall response rates (CR+PR) in Arm 1 (chemoradiation alone arm) and Arm 2 (neoadjuvant chemotherapy followed by chemoradiation arm) were 96% and 100%, respectively (complete response rates of 73.33% and 75%, respectively, and the partial response rates of 23.33% and 25%, respectively). The results were, therefore, similar to the reported literature [9,10]. The complete response rate was 87% and 97% in the chemoradiation alone arm and neoadjuvant followed by the definitive chemoradiation arm, respectively.…”
Section: Two Recent Work Have Compared This Modality Of Treatment Wit...supporting
confidence: 89%
See 2 more Smart Citations
“…The overall response rates (CR+PR) in Arm 1 (chemoradiation alone arm) and Arm 2 (neoadjuvant chemotherapy followed by chemoradiation arm) were 96% and 100%, respectively (complete response rates of 73.33% and 75%, respectively, and the partial response rates of 23.33% and 25%, respectively). The results were, therefore, similar to the reported literature [9,10]. The complete response rate was 87% and 97% in the chemoradiation alone arm and neoadjuvant followed by the definitive chemoradiation arm, respectively.…”
Section: Two Recent Work Have Compared This Modality Of Treatment Wit...supporting
confidence: 89%
“…concerning the use of neoadjuvant chemotherapy in this setting. In one study [10], the complete response rates noted were 97% and 87% in the neoadjuvant group and the chemoradiation group, respectively. There were no differences in overall survival between the two arms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Trials using short cycle chemotherapy with a chemotherapy cycle length of < 14 days and cisplatin dose intensities ≥ 25 mg/m 2 per week appear to be associated with an improvement in survival compared with those using a more prolonged cycle interval [6]. The initial results from two phase II studies [9,10] have been reported on patients who received NACT using weekly paclitaxel (60-80 mg/m 2 ) and carboplatin (AUC = 2) for 6 weeks followed by CCRT. Following NACT, a response rate of 67.8-72.7% was achieved, mostly partial responses.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional triweekly (once every 3 weeks) regimens of NACT followed by CCRT may not be superior to CCRT alone for the treatment of LACC [6][7][8]. Weekly regimens of NACT followed by CCRT may be superior to CCRT alone [6,9,10]. Moreover, particularly in developing countries, the incidence of advanced cervical cancer is high, and access to radiotherapy facilities is limited [11].…”
Section: Introductionmentioning
confidence: 99%